Percutaneous laser microdiscectomy in the treatment of thoracic intervertebral disc protrusions - Zorin, Mykola O.; Zorina, Tamara V. (Ukrainian Neurosurgical Journal, 2023)
One of the causes of thoracalgia is a protrusion of the thoracic intervertebral discs (IVD). Treatment of these protrusions is often ineffective. Objective: To improve the outcomes of treatment of thoracalgia caused by protrusions of the thoracic IVD, using the method of puncture laser microdiscectomy (PLM). Materials and methods. A retrospective analysis of treatment outcomes of 64 patients with thoracalgia at the "Endoscopic Neurosurgery" Medical Center in the period from 2000 to 2023 was carried out. The patients ranged in age from 24 to 67 years. There were 48 (75.5%) men, 16 (24.5%) women. Puncture laser microdiscectomy was performed in 42 patients under the control of a C-Arm operating fluoroscope (Philips, the Netherlands), 22 - under CT-assisted method (Toshiba, Japan). Results. In 10 cases, PLM was performed on two IVDs. The rate of positive results of treatment of thoracic IVD by the PLM method is 89%. The rate of excellent results was 71.4% in the group of operations under operating fluoroscope control, in the operations group under CT assisted method - 72.7%. Complications were registered only in 3 patients operated on under the fluoroscope control. Conclusions. Puncture laser microdiscectomy in case of thoracic IVD protrusions is an effective method for treatment of persistent thoracalgia. Performing PLM under CT assisted method does not increase the efficacy of the surgery, but it allows avoiding complications.